Spatio-Temporal Profiling of Aquatic Biodiversity in Stream Habitats in Gelephu Mindfulness City - Dorji, Ugyen; Moktan, Sonam; Tenzin, Ugyen; Sagar, Laxmi; Dorji, Rinchen; Subedi, Rupesh; Rai, Benath (Bhutan Journal of Research and Development, 2025)
Understanding aquatic biodiversity distribution across spatial and seasonal gradients is fundamental to evidence-based ecological planning, especially in rapidly transforming landscapes. This study presents a spatio-temporal profiling of fish, macroinvertebrate communities, and water quality across stream habitats in the proposed Gelephu Mindfulness City. Georeferenced aquatic plots were systematically distributed (200 m transects at 1 km intervals), capturing ecological variability during monsoon (August 2024) and post-monsoon (November 2024) seasons. Fish sampling employed cast nets, electrofishing, and seine nets, while macroinvertebrates were collected using D-frame kick nets and mesh-based scooping. Water quality profiling included DO, turbidity, TDS, pH, temperature, and flow velocity. Analytical procedures incorporated Shannon-Weaver diversity indices, species richness, and evenness, interpreted using multivariate ecological statistics in R. A total of 35 fish species (14 families) and 14 macroinvertebrate taxa (7 orders) were recorded. Post-monsoon sampling revealed higher fish abundance (N=849 vs. N=282), while macroinvertebrate diversity peaked during the monsoon (H’ = 1.90). Biodiversity patterns were strongly associated with hydrological gradients, substratum diversity, and habitat complexity. The findings inform ecological buffer zoning and season-sensitive infrastructure design, contributing to Bhutan’s biodiversity strategy and nature-positive urban development.